STUDI PEMANFAATAN BUAH PISANG MAS (Musa acuminata) DAN BUAH NAGA MERAH (Hylocereus polyrhizus) DALAM PEMBUATAN SELAI - Ade Herianto; Faizah Hamzah; Yusmarini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to obtain the ratio formulations of banana mas and red dragon fruit that selected in the preparation of jam based on SNI 3746: 2008. This research was carried out experimentally using completely randomized design (CRD) with five treatments and three replications in order to obtain fifteen experiment units. The treatments in this study include PN1 (100% banana), PN2 (75% banana and 25% dragon fruit), PN3 (50% banana and 50% dragon fruit), PN4 (25% banana and 75% dragon fruit), and PN5 (100% dragon fruit). Data obtained were treated by the analysis of variance followed by Duncan New Multiple Range Test (DNMRT) the level of 5%. The best jam of this study was PN3 (50% banana and 50% dragon fruit). The best jam results showed moisture 39,61%, acidity 4,78, total sugar content 50,82%, total dissolved solids 66,73% brix, crude fiber contents 0,34%. Total solids and total dissolved solids of the best jams results were meet SNI 3746:2008. The best jam had red colour of jam, banana taste was medium and dragon fruit taste was medium, banana flavor was weak and dragon fruit flavor was medium, and was soft. Keywords : Jam, banana mas, and red dragon fruit.